Anxiety and depression in parents of children with autism spectrum disorder during the first COVID-19 lockdown: Report from the ELENA cohort. (May 2022) - Miniarikova, Ela; Vernhet, Christelle; Peries, Marianne; Loubersac, Julie; Picot, Marie-Christine; Munir, Kerim; Baghdadli, Amaria
Abstract: Background: The Covid-19 pandemic had a strong impact on mental health in the general population. This study conducted during the first lockdown in France considered parents of children with Autism Spectrum Disorder (ASD) prospectively followed in the ELENA Cohort. Objectives: We aimed to (1) compare the Anxiety and Depression (AaD) levels during the lockdown between mothers and fathers, (2) compare the parent's AaD between the lockdown and the last ELENA follow-up visit, and (3) identify risk factors for parental AaD during lockdown among socio-demographic and children's clinical characteristics. Methods: The Hospital Anxiety and Depression Scale (HADS) was used to assess AaD in 134 parent's pairs. Parents also completed the Questionnaire about their living conditions during COVID-19, their child's interventions and perceived changes about their child's behaviors and sleep. Child's ASD severity, intellectual and socio-adaptive skills and parent's socio-demographic characteristics were collected from ELENA follow-up. Results: The parents' AaD levels were lower during the lockdown compared to the last ELENA visit that coincided in 96% with the child's ASD diagnosis. The AaD levels were more pronounced in mothers and significantly associated with the child's challenging behaviors, parents' teleworking and perceived knowledge about COVID-19. The perception of an insufficient knowledge was the only risk factor for mothers' AaD. Conclusion: Our findings highlighted the pertinence for an assessment of the mental health of main caregivers of children with ASD, consideration of their gender characteristics, and the importance of providing relevant information during pandemic. Future studies examining the pandemic long-term effects are needed. Trial registration number: NCT02625116. Highlights: Cross-sectional analysis of parental anxiety and depression (AaD) of children with confirmed ASD followed in a prospective cohort study during the COVID-19 pandemic. AaD were more pronounced for mothers than fathers during the lockdown. AaD levels for both parents were lower during the lockdown compared to the period corresponding to communication of the child's diagnosis of ASD prior to the pandemic. Mothers' levels of AaD were significantly associated with the child's challenging behaviors, teleworking at home, and their level of perceived knowledge about COVID-19. Mothers' perception of having insufficient knowledge about COVID-19 was a risk factor for AaD.